Impact of work-based HIV/AIDS interventions on knowledge, attitudes and perceptions of workers in a local municipality - Motsukunyane, Moipone Maureen (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.